Factors influencing Zimbabwean physiotherapy students in choosing physiotherapy as a career - T. Mkondo; W. Mudzi; N. P. Mbambo (AOSIS, 2007)
People join professions for different reasons and the same applies to physiotherapists. The aim of the study was to identify the reasons for choosing physiotherapy as a career by Zimbabwean physiotherapy students. The study used a descriptive cross-sectional design where a questionnaire was administered to 60 students. Data were collected on the demographics of the students and also on their rating on the importance of 12 factors for their influence in them choosing physiotherapy as a career.Three factors, which were, "the results I obtained at 'A'Level" (68%), "job availability"(67%) and "desire to help others"(60%), were rated by more than 60% of the students as factors that had been "very important" in their decision to pursue physiotherapy as a career. Two factors, "I always wanted to be a physiotherapist" and "I worked with or received treatment from a physiotherapist", were the only factors, which were rated by more than 70% of the students as no important in the students' decision. Using the paired t-test, no significant statistical differences were found between male and female students, in their rating of importance of all twelve factors, (p-value=0.01).